Unravelling the Methylene Blue Adsorption Mechanism on Doped and Nondoped Polyaniline: A Combined Molecular Modeling and Experimental Investigation - Souad Djellali; Amani Touati; Abderrahmane Semmeq; Maya Kebaili; Michael Badawi; Adrián Bonilla-Petriciolet (International Journal of Chemical Engineering)
A multiscale investigation including computational chemistry calculations and experimental studies was performed to elucidate and understand the methylene blue (MB) adsorption on polyaniline (PANI) from an aqueous solution. Static DFT and DFT-based ab initio molecular dynamics were used to characterize the intermolecular interactions of this dye molecule with nondoped and doped PANI. Experimental adsorption studies at different operating conditions were performed to complement the mechanism analysis of this adsorption system. Infrared spectroscopy studies and ab initio calculations showed the important role of π-π stacking and van der Waals interactions for the dye adsorption on PANI. Experimental results of MB adsorption on the PANI surface indicated that alkaline conditions were more favorable than acidic conditions where the MB adsorption capacity ranged from 9.91 mg/g at pH 1.8 to 23.16 mg/g at pH 10.9. Equilibrium adsorption studies with nondoped PANI revealed a fast removal of the dye molecules where the equilibrium adsorption was reached after 45 minutes. The kinetic parameters were calculated with the pseudo-second and pseudo-first order models, while the adsorption mechanism was analyzed using the intraparticle diffusion, Boyd, and Elovich models. Dye adsorption equilibrium was studied at pH 8 and 30 °C where Temkin, Freundlich, Langmuir, and Dubinin-Radushkevich (D-R) isotherm models as well as a statistical physics monolayer model were employed in data analysis. The saturation dye adsorption capacity was 40.2 mg/g where an inclined adsorption orientation of dye molecules on the PANI surface could be expected with an adsorption energy of 14.0 kJ/mol. This interaction energy clearly indicated that only physical interactions were involved in the MB dye adsorption mechanism, which was also confirmed by the calculations with the D-R isotherm model. These theoretical and experimental results are important to understand the dye adsorption properties of conductive polymers and to consolidate their application in the synthesis of new adsorbents and composites for water treatment.